2012
DOI: 10.1139/y2012-057
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sarco(endo)plasmic reticulum Ca2+-ATPase and calsequestrin gene expression in the heart

Abstract: The precise control of Ca2+levels during the contraction–relaxation cycle in cardiac myocytes is extremely important for normal beat-to-beat contractile activity. The sarcoplasmic reticulum (SR) plays a key role controlling calcium concentration in the cytosol. The SR Ca2+-ATPase (SERCA2) transports Ca2+inside the SR lumen during relaxation of the cardiac myocyte. Calsequestrin (Casq2) is the main protein in the SR lumen, functioning as a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…Reduced SERCA2 gene expression is frequently observed in experimental animal models and patients with end-stage HF [37], but its role in the initial stages of LV remodeling and HF progression remains unclear. For instance, Periasamy and colleagues [38,39] have shown that cardiomyocytes isolated from heterozygous SERCA2 knockout mice have a ~35% reduction in SERCA2 protein, a 30-40% reduction in the amplitude of the cytosolic Ca 2+ transient, and a 40 60% reduction in SR Ca 2+ load.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced SERCA2 gene expression is frequently observed in experimental animal models and patients with end-stage HF [37], but its role in the initial stages of LV remodeling and HF progression remains unclear. For instance, Periasamy and colleagues [38,39] have shown that cardiomyocytes isolated from heterozygous SERCA2 knockout mice have a ~35% reduction in SERCA2 protein, a 30-40% reduction in the amplitude of the cytosolic Ca 2+ transient, and a 40 60% reduction in SR Ca 2+ load.…”
Section: Discussionmentioning
confidence: 99%
“…RyR modulation from the SR lumen is achieved via triadin and junctin, which form complexes with calsequestrin (14,56,57,86). Calsequestrin is the most abundant Ca 2ϩ binding protein in the SR (9,160). CSQ2 (the mammalian cardiac isoform) binds Ca 2ϩ with a high capacity (ϳ60 -80 mol Ca 2ϩ /mol CSQ2) and a moderate affinity [dissociation constant (k d ) of ϳ1 mM] (109), thereby buffering SR Ca 2ϩ .…”
Section: Regulation Of Cicrmentioning
confidence: 99%
“…The rise in sarcoplasmic calcium causes contraction by Ca 2+ binding to troponin C, which relieves constraints on actin-myosin interaction and cross-bridge formation. With relaxation, 60%–80% of the sarcoplasmic Ca 2+ is actively transported into the sarcoplasmic reticulum lumen by the sarco(endo)plasmic reticulum Ca 2+ -ATPase pump (SERCA2a), while the remainder exits the cardiac myocyte by way of the Na + -Ca 2+ exchanger [7]. With heart failure, Ca 2+ uptake into the sarcoplasmic reticulum is impaired due to decreased expression of SERCA2a [7].…”
Section: Calcium Handling In the Failing Heartmentioning
confidence: 99%
“…With relaxation, 60%–80% of the sarcoplasmic Ca 2+ is actively transported into the sarcoplasmic reticulum lumen by the sarco(endo)plasmic reticulum Ca 2+ -ATPase pump (SERCA2a), while the remainder exits the cardiac myocyte by way of the Na + -Ca 2+ exchanger [7]. With heart failure, Ca 2+ uptake into the sarcoplasmic reticulum is impaired due to decreased expression of SERCA2a [7]. Activity of SERCA2a is decreased as well, due to an increased association of SERCA2a with its inhibitory regulator phospholamban for two reasons: first, normally, phosphorylation of phospholamban relieves SERCA2a inhibition by causing its dissociation from SERCA2a, but, in heart failure, there is less phosphorylation of phospholamban due to increased protein phosphatase 1 (PP1) activity [8]; second, the decreased SERCA2a/phospholamban ratio means that there is more phospholamban relative to SERCA2a, thus favoring SERCA2a inhibition.…”
Section: Calcium Handling In the Failing Heartmentioning
confidence: 99%
See 1 more Smart Citation